EKSISTENSI REPOWEREU: SEBUAH CLIMATE AMBITIONS UNI EROPA DAN IMPLIKASINYA TERHADAP STABILITAS GEOPOLITIK ENERGI RUSIA-EROPA - Azis, Abd; Marshanda Andrian, Tiara; Nurhaliza Akhrianti, Dinda (Department of International Relations Universitas Pertamina, 2022)
As the third largest carbon-emitting country in the world, the European Union has more responsibility to address the problem of preventing climate change. However, the climate management policies implemented by the European Union need to be more effective to achieve the long-term targets in the Paris Agreement. Responding to this, the European Union is planning a new policy, REPowerEU. REPowerEU is a follow-up effort from the European Union towards a clean energy transition and a form of Europe's anger towards Russia's geopolitical energy behaviour. In addition, the REPowerEU Plan is a tool the European Union uses to break away from energy dependence on Russia so that it can be more independent in determining foreign policy. This study aims to assess the impact of the implementation of the European Union's energy policy on Russian-European political stability. This study uses qualitative methods by collecting data through literature studies. This research is analyzed using the neoclassical realism paradigm based on energy geopolitics. It found that there are positive and negative impact in applying REPowerEU to decrease dependency of Russia’s energy supply to Europe.